Visualizing Mental Disorders in Iranian Cinema and Its Consequences for Public Attitudes Toward Mental Health: A Semiotic Analysis of Fereydoun Jeyrani’s Ghermez, Park Way, and Khefeghi - Ilani, Hengameh; Mahnaz Ronaghi; Laleh, Abdolhossein (Journal of Foresight and Health Governance, 2026)
The visualization of mental disorders in cinema plays a major role in shaping public attitudes toward mental health, psychiatric patients, and treatment institutions. Because media texts actively construct meaning rather than neutrally reflecting reality, cinematic portrayals can either reproduce stigma or challenge it. This qualitative study analyzes the representation of mental disorders in three films by Iranian filmmaker Fereydoun Jeyrani—Ghermez (1998), Park Way (2006), and Khefeghi (2016)—using Stuart Hall’s theory of representation, John Fiske’s multi-level communication model, and Roland Barthes’ semiotics. The analysis indicates a gradual shift from individualized, violence-centered depictions toward more structurally complex portrayals that increasingly highlight gendered power relations, social class dynamics, and institutional labeling processes. However, the recurring emphasis on tragic and violent outcomes still risks reinforcing stigma and fear-based interpretations of mental illness. The paper underscores the need to strengthen health communication discourse and encourage more responsible mental health portrayals in Iranian cinema.